Designing and Developing an Intelligent Congkak - Muhammad Safwan, Mohd Shahidan (2011)
Congkak is the nation's traditional game which could soon be forgotten if no serious attention is given to it, but literature survey has not yet found any research publication that mentioned the use of neural network algorithm (NN) on Congkak. Therefore the project want to try to rectify this issue by trying to develop an Intelligent Congkak System that also implemented NN and try answer research question such as this: “What is the best Congkak evaluation function for training NN for game playing?” and “Can Min-Max algorithm (MM) be speeded up by using NN as a forward-pruning method?”. This issues can solved by programming the Congkak system based on previous work on Mancala and NN system, and then recording the performance of the related algorithm. As a result: the project had created a Congkak system that had featured 3 Artificial Intelligence (AI) agent, and discovered that the combination of NN and MM is slower than MM alone.